THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, JOB STRESS AND WORK ENVIRONMENT ON ORGANIZATIONAL COMMITMENT (STUDY ON HOSPITAL EMPLOYEES IN SOUTH JAKARTA) - Kevin Citrasumidi; Rezi Erdiansyah (Graduate Program of Universitas Tarumanagara, 2024)
Productivity is something that companies always want to improve, including hospitals. Employees become assets and driving forces to achieve company goals. This research examines the influence of transformational leadership, work stress and the work environment on organizational commitment among hospital employees in South Jakarta. This research collected data from 130 respondents who were hospital employees in the South Jakarta area who were still working. This research is quantitative research with a non-probability-purposive sampling method and processed using partial least squares. The collected data was processed using SPSS version 28. The research results showed that transformational leadership and work stress had no effect on organizational commitment and the work environment had an effect on organizational commitment. Then transformational leadership, work environment, and work stress together influence organizational commitment. The managerial implications of this research suggest that hospital management can manage a conducive and supportive work environment as well as sufficient time and workload so that employees become more comfortable at work.